Empowered Empathetic Encounters: Building International Collaborations through researching writing in the context of South African Higher Education and Beyond - Farrell, Alison; Kane, Sandra; Salchak, Steven P; Dube, Cecilia M (South African Journal of Higher Education, 2016)
In this article we propose the idea of ‘Empowered Empathetic Encounters’ as a key success factor in the building of effective international inter-institutional collaboration. By Empowered Empathetic Encounters we mean the supported pivotal occasions where one meets with colleagues with whom one wishes to collaborate in face-to-face settings to try to understand, in a meaningful way, each other’s concerns and what it means to live and work in each other’s contexts. In our work we combine our personal and collective experiences with an analysis of these in the context of the existing literature. In this way, we wish to engage in a process of ‘thinking the cultural through the self’ (Probyn 1993) and ‘thinking theory through’ one’s own experience (Mann 2008, 10 – emphasis in original). We suggest that engaged encounters of this nature can provide the bedrock for successful, long-term collaboration.